Analysis of Consumptive Behavior on Purchasing Power During Shopee Flash Sale - Muzdalifah, Muzdalifah; Purnomo, Agus; Zahra Maulida, Atika (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Advances in information technology cause changes in all aspects of life, one of which is in the aspect of trading, buying and selling trades can be done online. One of the online shopping media is shopee. Shopee is an online shopping platform that is familiar to the community, shopee is an online shopping platform that is popular with all people ranging from teenagers, and adults, to the elderly. The purpose of this study is to analyze consumptive behavior towards purchasing power during shopee flash sales. The type of research used is a qualitative approach with primary and secondary data sources with three active shopee user speakers, using data collection techniques in the form of observation, interviews, and documentation. And using data analysis techniques in the form of descriptive data analysis techniques